2022
DOI: 10.1111/csp2.12783
|View full text |Cite
|
Sign up to set email alerts
|

Offshore and coastline migration of radio‐tagged Nathusius' pipistrelles

Abstract: The wind energy-bat conflict is well documented for the onshore sector, with high numbers of casualties, specifically for migratory bat species. Offshore wind turbines might be a threat to bats as well, yet offshore bat migration is poorly documented. Accordingly, potential conflicts between bat conservation and offshore wind energy production are difficult to evaluate. Here, we used automated radio-telemetry to track 50 km continuous offshore movements of two Nathusius' pipistrelles (Pipistrellus nathusii) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“… 2018 , Bach et al. 2022 ), some of which are also heavily used for wind energy production (Nunalee and Basu 2014 , Wieringa et al. 2021 ).…”
Section: Current Practice Of Avoidance–mitigation–compensation Hierar...mentioning
confidence: 99%
“… 2018 , Bach et al. 2022 ), some of which are also heavily used for wind energy production (Nunalee and Basu 2014 , Wieringa et al. 2021 ).…”
Section: Current Practice Of Avoidance–mitigation–compensation Hierar...mentioning
confidence: 99%
“…Beyond 85 km from shore the proportion of occurrences early in the night becomes greater than the proportion late at night causing a decrease in the average time of occurrence, indicating that the recorded bats do not cross the North Sea in one night. Interestingly, Bach et al (2022) found travel distances of radio tracked Nathusius' pipistrelles between 103 -131 km per night. Flight mechanical theory however predicts that bats can fly longer distances (Hedenström 2009) which would allow them to cross the North Sea in one night.…”
Section: Spatio-temporal Occurrence In Autumnmentioning
confidence: 99%
“…Despite their importance, very little is known about different properties of long-range bat movement. Bats perform seasonal migrations spanning thousands of kilometres which, so far, were only studied using Lagrangian sampling methods (single individuals tracked over large areas and long time periods, Bach et al, 2022;Caprio et al, 2020;Cryan et al, 2014;Hutterer et al, 2005;Lagerveld et al, 2014;O'mara et al, 2014, 2019Petit & Mayer, 2000;Russell et al, 2005;Sullivan et al, 2012;Villa & Cockrum, 1962;Wilkinson & Fleming, 1996). These methods rely on sparse, sporadic observations of usually small number of individuals, which provide a very limited view of bat migration, preventing comprehensive, largescales analyses (Fleming, 2019).…”
Section: Introductionmentioning
confidence: 99%